Duo-ethnography as the Qualitative Inquiry in Small Family Business Research = Wykorzystanie duo-etnografii w badaniach jakościowych małych przedsiębiorstw rodzinnych - Sułkowski, Łukasz; Marjański, Andrzej (Zielona Góra: Faculty of Economics and Management Press)
The research methodology of family businesses is increasingly becoming the subject of scientific discussion that shows how difficult and complex task it is. Research area is located on the border of several disciplines, which raises significant methodological problems. Qualitative methods are useful for studying the problems of small family businesses, in particular related to the sphere of issues of identity, culture, values and the relationship between the family and the company.
Keywords: nauki o zarządzaniu; przedsiębiorstwo rodzinne; metoda badawcza; badania jakościowe; management sciences; family business; research method; qualitative research